Political Elite of Transnistria: on a Question of Prerequisites of Emergence of the Republic - Sergey Viktorovich Oleynikov (Управленческое консультирование, 2018)
Political reformatting of once uniform Soviet space, the prerequisite of emergence of ideological breaks in the countries of the new abroad which led in some cases to declaration of the republics, and also their political and legal essence still remains a subject of dispute of political, economic, but also scientific elite. The geopolitical resonance of the processes connected with kindling and then settlement of political conflicts in the Post-Soviet territory is usually caused by opposite ideological moods which are cultivated actively by political elite of this or that region. It should be noted that in most cases influence of large information institutes in processes of political opposition substantially accelerated ideological delimitation and aggravated a political situation in new state educations. While local mass media carried out the consolidating function and strengthened spiritual unity of the population of certain regions. For this reason in processes of formation of new system of identity the dominating role was played by a regionalism factor, having pushed aside national, cultural, linguistic identification markers. The analysis of cultural and language, historical and other factors not so much of the population, how many the power structures initiating more than two decades ago revival of Dnestr statehood in the context of special social and demographic characteristics of representatives of political elite of Transnistria is a necessary condition of adequate perception of a current state of the young republic and understanding of the reasons of an ideological break and political opposition on coast of Dnieste